Review of hartmut rosa's book alienation and acceleration: Towards a critical theory of late¬modern temporality (Revista Estudos Culturais, 2015)
In Alienation and Acceleration. Towards a Critical Theory of LateModern Temporality Hartmut Rosa briefly recapitulates and expands his Theory of Social Acceleration. This expansion is made first through the analyse of the decelerating elements of the acceleration tendency and, second, through the analysis of the consequences of acceleration for the actual social Critical Theory, whose questions put and answers given until now wouldn’t present a solution for the loss of credibility of the project of modernity, once that social acceleration succumbed and instrumentalized the promissed possibility of autonomy. Looking for an answer the question of what would be a fullfilled life, Rosa retraces the context of the development of dif erent categories of alienation, depicting in his theory an extremly relevant and growing social tendency of modern times.